First record of Siamspinops Dankittipakul & Corronca, 2009 from India, first description of the female of Makdiops shevaroyensis (Gravely, 1931), and a catalogue of Indian selenopid fauna (Araneae, Selenopidae) - Sankaran, Pradeep M.; Kadam, Gautam; Sudhikumar, Ambalaparambil Vasu; Tripathi, Rishikesh (Zootaxa, 2022)
The selenopid genus Siamspinops Dankittipakul & Corronca, 2009 is recorded for the first time from India. Siamspinops garoensis Kadam, Tripathi & Sankaran, 2022 sp. nov., based on male and female specimens, is described and illustrated in detail. The unknown female of Makdiops shevaroyensis (Gravely, 1931) is described and illustrated for the first time, and a catalogue and distribution maps of the Indian selenopid species are provided.